PEMBERIAN KOMPOS KULIT BUAH KAKAO DENGAN BEBERAPA DOSIS NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Adven Mario Sihombing; Al Ikhsan Amri; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to determine effect of composting of cocoa fruit peel with some NPK dose and get the best treatment on the growth seedling of oil palm (Elaeis guineensis Jacq.) in the main nursery. This research was conducted in the experimental fields of Agriculture faculty, Riau University, Bina Widya Street Km 12,5 Simpang Baru, Tampan Pekanbaru. Research was held 4 months, starting from February 2015 until May 2015. Research using experiment design with Completely Randomize Design (CRD) consisting of 5 treatments every treatment was repeated 4 times, and retrieved 20 units of experiment, each unit consisting of 2 seed. The total were 40 seed and observed doing to all seed, the treatment is combination cocoa fruit peel compost with some NPK dose. Parameters observed were the increase of seeds height, increase of leaves, increase of hump convolution, volume of root, root shoot ratio and dry weight. Data were analyzed statistically using ANOVA and followed by DNMRT at level of 5%. The results showed that composting of cocoa fruit peel with some NPK dose significant effect on increase of seeds height, increase of hump convolution, volume of root, root shoot ratio and dry weight but not significant on increase of leaves. Composting of cocoa fruit peel 150 g/polybag + 1 NPK dose give the best growth oil palm seed. Keywords : Palm oil, cocoa fruit peel compost and NPK.